2023
DOI: 10.3390/ijerph20021425
|View full text |Cite
|
Sign up to set email alerts
|

Ghana’s Adherence to PASCAR’s 10-Point Action Plan towards Hypertension Control: A Scoping Review

Abstract: The continuous increase in the prevalence of hypertension in Ghana has led to various interventions aimed at controlling the disease burden. Nonetheless, these interventions have yielded poor health outcomes. Subsequently, the Pan-African Society of Cardiology (PASCAR), established a 10-point action plan for inclusion in policies to aid control of hypertension. This scoping review assessed the adherence of health policies to the 10-point action plan towards hypertension control/reduction in Ghana. Eight health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…In 2022, Ghana released the second edition of the National Policy for NCDs, including hypertension-related conditions, following the first edition in 2012 [ 29 ]. According to a study evaluating Ghana’s adherence to PASCAR recommendations (which include many strategies that were included in the 2012 NCDs policy), Ghana is still behind in terms of implementing changes that could ultimately improve BP outcomes for patients [ 8 ]. The government of Ghana should increase healthcare spending from the current 3.5% to at least 15% of the gross domestic product (GDP), as it pledged in the 2001 Abuja Declaration [ 30 , 31 ], to fund projects on its health agenda and ensure strategic allocation and accountability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Ghana released the second edition of the National Policy for NCDs, including hypertension-related conditions, following the first edition in 2012 [ 29 ]. According to a study evaluating Ghana’s adherence to PASCAR recommendations (which include many strategies that were included in the 2012 NCDs policy), Ghana is still behind in terms of implementing changes that could ultimately improve BP outcomes for patients [ 8 ]. The government of Ghana should increase healthcare spending from the current 3.5% to at least 15% of the gross domestic product (GDP), as it pledged in the 2001 Abuja Declaration [ 30 , 31 ], to fund projects on its health agenda and ensure strategic allocation and accountability.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure objectivity, the 10 steps recommended instituting a monitoring and evaluation system for all the above activities [ 7 ]. Nonetheless, a recent study in Ghana reported poor adherence to PASCAR recommendations and noted that there remains a long way to go before achieving the goal of 25% hypertension control [ 8 ].…”
Section: Introductionmentioning
confidence: 99%